The Nuclear Order in check... by whom? - Vera, Nevia; Colombo, Sandra; Guglielminotti, Cristian (Mural Internacional, 2023)
When does an international regime weaken or enter into contradiction? What is happening to the global nuclear order and why is it said to be in crisis? This article addresses possible answers to these questions in order to contribute to the debate surrounding the apparent weakening of the International Nonproliferation Regime. It does so by analyzing first the 2005 agreement between the United States and India and the subsequent support for the latter’s entry into the Nuclear Suppliers Group. Second, the AUKUS military alliance sustained around the provision of nuclear-powered submarines by the United States and the United Kingdom to Australia, which is not without proliferation risks. We argue that the weakening of the nuclear order is occurring not only because of the potential for proliferation in countries such as Iran but also because of the contradictions and non-compliance of the nuclear powers themselves. Received on: 28 Feb. 2023 | Accepted on: 25 Oct. 2023.